The epidemiology of alcohol consumption in Ethiopia: a systematic review and meta-analysis - Getinet Ayano (Substance Abuse Treatment, Prevention, and Policy, 2019)
Abstract Background Globally, excessive alcohol consumption is a major public health problem and is associated with social, mental, physical and legal consequences. However, no systematic review and meta-analysis has been performed to report the consolidated magnitude of alcohol consumption in Ethiopia. Methods PubMed, EMBASE, and SCOPUS were systematically searched to identify pertinent studies. Subgroup and sensitivity analysis was conducted and Cochran’s Q- and the I2 test were used to assess heterogeneity. Publication bias was evaluated by using Egger’s test and visual inspection of the symmetry in funnel plots. Results We included 26 articles with a total of 42,811 participants. The pooled current and lifetime prevalence of alcohol consumption was 23.86% (95%CI; 17.53–31.60) and 44.16% (95%CI; 34.20–54.62), respectively. The pooled prevalence of hazardous alcohol consumption was 8.94% (95%CI; 3.40–21.50). The prevalence of hazardous alcohol consumption was remarkably higher in men (11.58%) than in women (1.21%). The prevalence of current and lifetime alcohol consumptions among university students were 22.08% & 38.88% respectively. The pooled data revealed that male sex was found to be a significant predictor of hazardous alcohol consumption (OR 10.38; 95%CI 3.86 to 27.88) as well as current (OR 2.45; 95%CI 1.78 to 3.38) and lifetime (OR 2.14; 95%CI 1.39 to 3.29) consumption. The magnitude of alcohol consumption among university students was apparently lower than the magnitude in other population of the country. The current study suggested a remarkable recent increment in the magnitude of hazardous alcohol consumption in Ethiopia. Conclusion The current study revealed that the prevalence of alcohol consumption in Ethiopia is comparable with the global estimates of alcohol consumption from the World Health Organization (WHO). The prevalence of hazardous alcohol consumption was remarkably higher in men (11.58%) than in women (1.21%). Male sex was found to be a significant predictor of alcohol consumption. The present study also suggested considerable recent increment in the magnitude of hazardous alcohol consumption in Ethiopia.